Peningkatan Peran serta Masyarakat dalam Pemanfaatan Lahan Pekarangan melalui Penanaman Pohon Ekonomis di Desa Ciherang, Bogor, Jawa Barat - Dafit Ariyanto; Saijo Saijo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The yard is a green open space that has economic value. The society's devotion was conducted on Sunday, October 22, 2017, in Ciherang Village, Bogor, West Java. The purpose of community service was to grow the spirit of public awareness of the importance of preserving the environment within the scope of the family and the surrounding environment. The method used was FGD (Focus Group Discussion) method and application. The research used descriptive analysis. The results showed that the high enthusiasm and awareness about environmental awareness in the field of the yard. Overall awareness raising of the community requires cooperation between various parties.